EFFECTIVENESS OF LIME (Citrus aurantifolia) AND TOMATO (Solanum lycopersicum) REDUCING LEAD LEVELS AND CADMIUM IN BLOOD MUSSELS (Anadara granosa) - Lismawati Lismawati; Mirna Ilza; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT          Blood mussels are one of the marine life that live in filter feeders. Because the way of life of shellfish that immerse themselves in mud causes a high content of heavy metals in the shellfish body, one of which is Lead (Pb) and Cadmium (Cd). The reduction of heavy metal levels can be done using citric acid found in lime and tomato fruits. This study aims to determine the effect of soaking blood mussels using a solution of lime and tomato fruit on reducing the levels of heavy metals Pb and Cd in blood mussels. The type of research used was experimental research using Non-Factorial RAL with 4 treatments, namely, P0 (soaking with 25% aquades), P1 (soaking with 25% lime), P2 (soaking with 25% tomatoes), and P3 (soaking with 25% combination of lime and tomato). The parameters tested included tests of heavy metal levels of Pb and Cd. Results showed Pb metal levels in blood mussels before soaking with lime and tomatoes of 4.00 ppm and Cd levels of 4.01 ppm. After soaking with lime, the Pb metal content in blood mussels dropped to 1.85 ppm and Cd levels of 1.23 ppm. Then soaking with tomato fruit Pb metal content in blood mussels dropped to 2.18 ppm and Cd levels to 2.10 ppm, while soaking a combination of lime and tomato Pb heavy metal content in blood mussels dropped to 1.88 ppm and Cd levels dropped to 1.75 ppm. Keywords: Blood mussels, Heavy metals, Lime, Tomatoes